Management of Various Types of Fistula-in-ano by Medicated Seton (Ksharasutra) and Open Fistulotomy- A Comparative Study - Deepak Pankaj; Nitesh Kumar; Sweta Muni; Vibhuti Bhushan; Nitesh; Pradyot Shahi; Nirupam; Priyanka Chaubey (International Journal of Anatomy Radiology and Surgery, 2020)
Introduction: Fistula-in-ano is treated by various modalities in modern era, but still today no single modality has proved to be complete cure for it. Ksharasutra is being practiced in Indian system of medicine since ancient time for management of anorectal disorders. Aim: To evaluate the efficacy of ksharasutra in comparison to standard open fistulotomy in the management of fistula-in-ano and to find better patient compliance. Material and Methods: This prospective study was planned and conducted among 60 patients who reported with fstula-in-ano to IGIMS, Patna. Patients were divided into two groups with 30 patients in each group on the basis of treatment plan i.e., open fistulotomy in one group and ksharasutra in the second group. The present study measured and compared operating time, healing time and hospital stay as primary variables and postoperative complications as secondary variables. Patient was followed at regular intervals of 1 week, 1 month and 3 months. The postoperative pain was evaluated using Visual Analogue Scale (VAS) ranging from 0 to 10 with mild cases with value of 0-3, moderate from 4-7 and severe from 8-10. Data so obtained was evaluated using the chi-square test with p <0.05 as significant value. Results: Operating time was significantly lower in ksharasutra group as compared to fistulotomy group, average of 38 minutes in fistulotomy group while average of 16 minutes in ksharasutra group (p=0.0021). Average healing time in patients who underwent fistulotomy was 22 days, and in Ksharasutra group it was 43 days (p=0.014). Duration of hospital stay was more in fistulotomy group while in ksharasutra group, it was an Out-Patient Department (OPD) procedure with observation time of one to two hours postprocedure (p=0.001). Among postoperative complications, pain (measured on VAS) was significantly high (36.7%) in patients with fistulotomy as compared to those with ksharasutra, (13.3%) while infection was slightly higher in fistulotomy group. Recurrence was observed in 16.7% of cases in fistulotomy group while it was 3.3% in ksharasutra group. Conclusion: Anal fistula causes physical as well as psychological burden to the patient. At present when there are various treatment options for anal fistula, authors have concluded that Ksharasutra with less complications along patient compliance is a cost effective option in this setting as postoperative complications, longer hospital stay adds extra economic burden to patient.